Better Regulation Impact on EU Law-Making - Gallizioli, Giorgio (Teisė, 2020)
This paper aims to analyse these new rules introduced by the EC. The purpose is to evaluate whether or not these changes have altered the original institutional design significantly and to assess its impact on the “Community method”, in other words on the EC prerogative to initiate the law-making machinery.